PERANCANGAN SISTEM PENGAMBILAN DAN PENGUNGGAH DATA GAMBAR PADA E-NOSE MEMPERGUNAKAN RASPBERRY PI - Pharmayeni Pharmayeni; Zulhamidi Zulhamidi; Isra Mouludi (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
The more sophisticated of the electronic equipment, so the for us to provide information to the public, in this case to provide any information including information about alcohol content in drinks to the public fast dan directly, we can use the internet and a website which can provide information in the form of text,picture, audio or video. In this research we will use the MQ-3 alcohol sensor, the camera and Raspberry pi which the whole system is a live stream means that no data is edited, any data readable by sensor then the data that is directly uploaded to the webserver. The method in this design is used two Raspberry pi3 which one function as client and the other as server, on client side paired a Raspberry camera (picamera), data acquisition AD / DA, and MQ-3 sensor while on server side there apache, mysql with client-server communication system and using python programming language and socket programing. The results of the design show that the MQ-3 and picamera sensors are running well and data can be sent from client to server.